UV rays Decrease Foliar pH in Cress (Lepidium Sativum) and Modify NIR Spectrum - Giorgio Masoero; Alberto Cugnetto; Giuseppe Sarasso; Giovanni D’Amore; Giusto Giovannetti; Marco Nuti (Journal of Agronomy Research, 2020)
An experiment on watercress (Lepidium sativum) 42 d days after sowing was set up to evaluate the effect of UVAB radiation on foliar pH and on NIR tomoscopy. The effect of 8 h of UV exposure (about 500 µWcm-2) was clear, causing a reduction in the foliar pH of 6.0%, compared to the contemporary control group (5.22 vs. 5.56). When the treated leaves were returned to white light, their pH rose by 1.7% (5.31), reaching the same level as leaves grown outdoors (5.33). On the basis of the NIR spectra, the leaves of the plants grown outdoors were recognized 100%, that is, more than the control leaves (87%) and the plants treated with UV on the day of measurement (81%). However, the effect of the UV marking on the leaves is not permanent as, after the UV treatment, the leaves returned to white light were classified at 61%, which is a greater value than the 37% of overlapping between the two groups. The foliar pH was highly correlated with the NIR spectra, with R2 0.43. These results corroborate the hypothesis of the influence of the solar cycle on the variation of the pH of leaves in plants, which we believe may have played a major role in past agricultural pandemics. These results call for the introduction of the pH test for the evaluation of resistance to pathogens. From the environmental point of view, the foliar pH could be enlisted as an in vivo long-time indicator of the response of plants to climate changes.
Keywords: UV